Pengendalian Kekerasan Anak Melalui Pembentukan dan Pendampingan Paralegal Pada Komunitas/Organisasi Perguruan Pencak Silat di Kecamatan Munjungan, Kabupaten Trenggalek, Provinsi Jawa Timur - Muksin, Muksin; Ula, Siti Khoirotul; Manaqib, Ulil (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
Trenggalek Regency and especially Munjungan Sub-district have experienced a decrease in conflicts between martial arts schools, but several conflicts still occur that originate from the motive of disputes between martial arts schools. These conflicts often involve children and teenagers who are supposed to be the productive next generation. At the same time, administrators of martial arts colleges who have previously been accustomed to dealing with or carrying out assistance practices when their members are in conflict, have actually also performed tasks that are close to the duties and functions of a paralegal. Therefore, it is important to carry out community service activities that are empowering in this area. The purpose of this community service activity is the formation of paralegals in the community or martial arts college organisation to control child abuse and legal advocacy to the community. The method used is the Asset-Based Community Development (ABCD) method. The results of this activity reported that: as an initial condition, the paralegal formation participants have great potential but still have limitations in terms of understanding the law, conflict mediation and child protection. Using an Asset-Based Community Development (ABCD) approach involving asset identification, participatory planning, and intensive training throughout the programme, paralegals were involved in community education activities, such as anti-violence in the internal community. This process was inclusive. The training was designed to not only increase individual capacity but also build synergy between groups in peacefully handling conflicts. The conclusion of this activity provided significant development in paralegal capacity and positive impact in the community. Paralegals who were trained have followed up and started to intensify in advocacy and mentoring.